L’eau dans la fabrique de la ville - Lætitia Borau (Mélanges de la Casa de Velázquez)
Since 2013, new investigations (prospecting, architectural surveys, archaeological soundings) have been carried out on the considerable water works at Baelo Claudia: this small Roman town had three aqueducts, several settling ponds and fountains, at least one water tower and a variety of cisterns, lead pipes and sewers. This first situation report focuses chiefly on the water supply system and reveals the existence of original Roman hydraulic engineering devices. This work places in perspective the development of the town’s water supply, mainly during the High Empire, by examining the layout of the works, construction techniques, architectural models or even their chronologies. Little by little a new image of Baelo Claudia is emerging, in which water holds an important place in the fabric of this town in the extreme south of the Iberian Peninsula.